Ratchet-Rasquache Activism: Aesthetic and Discursive Frames within Chicago-Based Women-of-Color Activism. (20th September 2020) - Gonzales, Teresa Irene
Abstract: Extending the rich literature about women-of-color activism, this article analyzes the ways Chicago-based Chicanas and Black women maintain, build, and expand low-income residents' access to and ownership of the city. I draw on 30 months of community-engaged, ethnographic fieldwork within high-poverty Mexican- and African-American neighborhoods and on interviews with 22 women-of-color activists across Chicago. Combining the cultural signifiers "ratchet" and "rasquache, " I highlight the strategic use of discursive and aesthetic frames to disrupt negative narratives of these women's activism and their often-vilified communities. As a framework, ratchet-rasquache activism counters urban development practices that marginalize Black and Chicana/o/x communities. Emerging from African-American communities, "ratchet" connotes unruliness and low-class behavior. In Mexican communities, "rasquache" similarly connotes negative or low-class behavior but also means making the most with the tools one has. Both concepts, rooted in working-class sensibilities, can subvert narratives of racial uplift and reject normative whiteness as the standard for both activism and community development. Deploying "ratchet" and "rasquache" as positive attributes, Chicago-based women-of-color activists used nonhierarchical community-organizing tactics to operate as neighborhood strategists. Acknowledging the strength and expertise within marginalized, impoverished communities, they embraced a working-class, asset-based, ratchet and rasquache strategy, while striving to build something from something.